The origin of UV‐optical variability in AGN and test of disc models: XMM‐Newton and ground‐based observations of NGC 4395. Issue 4 (May 2016) - McHardy, I. M.; Connolly, S. D.; Peterson, B. M.; Bieryla, A.; Chand, H.; Elvis, M. S.; Emmanoulopoulos, D.; Falco, E.; Gandhi, P.; Kaspi, S.; Latham, D.; Lira, P.; et al.
Abstract: The origin of short timescale (weeks/months) variability of AGN, whether due to intrinsic disc variations or reprocessing of X‐ray emission by a surrounding accretion disc, has been a puzzle for many years. However recently a number of observational programmes, particularly of NGC 5548 with Swift, have shown that the UV/optical variations lag behind the X‐ray variations in a manner strongly supportive of X‐ray reprocessing. Somewhat surprisingly, the implied size of the accretion disc is ∼3 times greater than expected from a standard, smooth, Shakura‐Sunyaev thin disc model. Although the difference may be explained by a clumpy accretion disc, it is not clear whether the difference will occur in all AGN or whether it may change as, eg, a function of black hole mass, accretion rate, or disc temperature. Measurements of interband lags for most AGN require long timescale monitoring, which is hard to arrange. However for low mass (<10 6 M⊙ ) AGN, the combination of XMM‐ Newton EPIC (X‐rays) with the optical monitor in fast readout mode allows an X‐ray/UV‐optical lag to be measured within a single long observation. Here we summarise previous related observations and report on XMM‐ Newton observations of NGC 4395 (mass 100 times lower, accretion rate ∼20 times lower than for NGC 5548). We find that the UVW1 lags the X‐rays by ∼470 s. Simultaneous observations at 6 different ground based observatories also allowed the g‐band lag (∼800 s) to be measured. These observations are in agreement with X‐ray reprocessing but initial analysis suggests that, for NGC 4395, they do not differ markedly from the predictions of the standard thin disc model. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)